Sustainable boat transportation throughout electrification of propulsion systems: Challenges and opportunities (2019)
Global use of carbon-based fuels increased by 1.6 % in 2017 and continued increasing in 2018, after managing to maintain emissions flat between 2014-2017. This trend deviates from the emissions trajectory required to fulfill the climate change goals to maintain the earth's temperature below 2-degrees. The transport sector accounts for about a quarter of these emissions but its the sector with the highest dependence on fossil-fuels. In order to reduce emissions, several approaches have been taken, from increasing fuel efficiency to the use of alternative fuels altogether. The most recent trend leans towards electrifiying the transport sector. High penetration of mature renewable energy technologies such as wind and solar photovoltaics as well as energy storage improvements are leading the way. While mass adoption of electric-propulsion systems for boats are still years away, recent pilot projects suggest that electrifying boats for passenger transportation may be not only a sustainable transport solution but its lower operation costs could facilitate its penetration on densely populated coastal and river cities where conventional public transport systems are reaching their full capacity. © 2019 IEEE.